Conflict treatment in the equal employment opportunity human resource management - Dajnoki, Krisztina (Acta Scientiarum Socialium, 2011)
Human resource management is a new scientific field, the content of which only developed in the last decades of the twentieth century. In a relatively short period it evolved spectacularly. Private knowledge, typical approaches, and methods appeared; it has its own research field and distinct scientific trends, even its own schools. A different orientation may appear towards new, special areas in the twenty-first century. A typical, prospective trend may occur in the field of handicapped and changed-capacity labor employment and its human resource management. The research objective of the dedicated „Equal Employment Opportunity Human Resource Management” is to reveal employment and management tasks, characteristics, processes, and methods. The aim of this article is to present conflict management at organizations that employ disabled persons.
Keywords: handicapped pensioner; changed capacity labor; conflict; communication; human resource management